Peran Lembaga yang Mendukung Penelusuran Alat Bukti Tindak Pidana Pencucian Uang yang Menggunakan Cryptocurrency - Susanto, Asmara Nova; Afifah, Wiwik (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The purpose of writing the journal is to analyze the role of law enforcement agencies in tracing money laundering cases using Cryptocurrency. The perpetrators of the crime are trying to find a place to launder money or a place that cannot trace the assets resulting from the crime. Cryptocurrency is a form of asset that is difficult to trace because it has anonymous and decentralized properties. The method of writing this journal uses normative juridical. The results of the study are that handling TPPU using Cryptocurrency in Indonesia requires the role of PPATK, OJK, KPK, BAPPEBTI, Polri, Prosecutor's Office, Financial Action Task Force (FATF), Interpol, and Financial Intelligence Units (FIUs). The crucial role that must be carried out is coordination for tracing crypto assets, knowing the motives for the flow of funds, analyzing transaction patterns, obtaining evidence, and knowing the parties involved. However, the defendant is the one who is asked to prove assets that are not the result of a crime, because in TPPU the evidentiary system uses reverse proof.